Micellar Choline-Acetyltransferase Complexes Exhibit Ultra-Boosted Catalytic Rate for Acetylcholine Synthesis—Mechanistic Insights for Development of Acetylcholine-Enhancing Micellar Nanotherapeutics - Jangra, Jatin; Baidya, Anurag T. K.; Kumar, Rajnish; Dante, Davide; Darreh-Shori, Taher (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Choline-acetyltransferase (ChAT) is the key cholinergic enzyme responsible for the biosynthesis of acetylcholine (ACh), a crucial signaling molecule with both canonical neurotransmitter function and auto- and paracrine signaling activity in non-neuronal cells, such as lymphocytes and astroglia. Cholinergic dysfunction is linked to both neurodegenerative and inflammatory diseases. In this study, we investigated a serendipitous observation, namely that the catalytic rate of human recombinant ChAT (rhChAT) protein greatly differed in buffered solution in the presence and absence of Triton X-100 (TX100). At a single concentration of 0.05% (v/v), TX100 boosted the specific activity of rhChAT by 4-fold. Dose–response analysis within a TX100 concentration range of 0.8% to 0.008% (accounting for 13.7 mM to 0.013 mM) resulted in an S-shaped response curve, indicative of an over 10-fold boost in the catalytic rate of rhChAT. This dramatic boost was unlikely due to a mere structural stabilization since it remained even after the addition of 1.0 mg/mL gelatin to the ChAT solution as a protein stabilizer. Furthermore, we found that the catalytic function of the ACh-degrading enzyme, AChE, was unaffected by TX100, underscoring the specificity of the effect for ChAT. Examination of the dose–response curve in relation to the critical micelle concentration (CMC) of TX100 revealed that a boost in ChAT activity occurred when the TX100 concentration passed its CMC, indicating that formation of micelle–ChAT complexes was crucial. We challenged this hypothesis by repeating the experiment on Tween 20 (TW20), another non-ionic surfactant with ~3-fold lower CMC compared to TX100 (0.06 vs. 0.2 mM). The analysis confirmed that micelle formation is crucial for ultra-boosting the activity of ChAT. In silico molecular dynamic simulation supported the notion of ChAT–micelle complex formation. We hypothesize that TX100 or TW20 micelles, by mimicking cell–membrane microenvironments, facilitate ChAT in accessing its full catalytic potential by fine-tuning its structural stabilization and/or enhancing its substrate accessibility. These insights are expected to facilitate research toward the development of new cholinergic-enhancing therapeutics through the formulation of micelle-embedded ChAT nanoparticles.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Cholinergic signaling; Choline-acetyltransferase; Acetylcholinesterase; Catalytic rate; Critical micelle concentration